Do I know you? : a faceblind reporter's journey into the science of sight, memory, and imagination - Dingfelder, Sadie (Little, Brown Spark, Hachette Book Group, 2024)
"Science writer Sadie Dingfelder has always known that she's a little quirky. But while she's made some strange mistakes over the years, it's not until she accosts a stranger in a grocery store (who she thinks is her husband) that she realizes something is amiss. With a mixture of curiosity and dread, Dingfelder starts contacting neuroscientists and lands herself in scores of studies. In the course of her nerdy midlife crisis, she discovers that she is emphatically not neurotypical. She has prosopagnosia (faceblindness), stereoblindness, aphantasia (an inability to create mental imagery), and a condition called Severely Deficient Autobiographical Memory. What Dingfelder learns about the brain captivates her. What she learns about the places where her brain falls short forces her to reinterpret major events from her past and grieve for losses she didn't even know she'd had"--